2018
DOI: 10.1155/2018/3258123
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Sulfuric Acid Corrosion Mechanism for Concrete in Soaking Environment

Abstract: is paper chooses the apparent diffusion coefficient for OH − (hydroxyl ion) for concrete as an index to evaluate the corrosion degree of concrete subjected to sulfuric acid. Based on the reaction boundary layer theory, a sulfuric acid corrosion model for concrete was established and verified through experiments. e experiment design and data processing of sulfuric acid corrosion tests for concrete were carried out using uniform test design and nonparametric regression. Effects of water-cement ratio and pH value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The fibers and aggregates were exposed as the corrosion cycles increased. In the later stage, the M specimens under environment I seemed to be more damaged than the specimens under environment II [ 47 ]. Both M and P specimens became soft after 12 acid-alkaline cycles, while the surface remained a little bit harder in environment II.…”
Section: Resultsmentioning
confidence: 99%
“…The fibers and aggregates were exposed as the corrosion cycles increased. In the later stage, the M specimens under environment I seemed to be more damaged than the specimens under environment II [ 47 ]. Both M and P specimens became soft after 12 acid-alkaline cycles, while the surface remained a little bit harder in environment II.…”
Section: Resultsmentioning
confidence: 99%
“…Correspondingly, the mix designation B5R15 showed a lesser surface erosion than that of the control mix, as shown in Figure 10. Min & Song (2018) also reported that the crucial corrosion can be indicated in the yellow color area that appeared on the exposed surface of the cement composite to sulfuric acid solution.…”
Section: Weight Lossmentioning
confidence: 96%
“…The most negative effect on cementitious materials is given by sulfuric acid due to the synergistic effect of acid attacks and sulphates [27][28][29]. By the reaction among calcium aluminates (C 3 A) and portlandite (CH) with sulfates ions, two major expansive products are formed: secondary ettringite (Ca 6 Al 2 (SO 4 )3(OH)12.26H 2 O, a principal destructive compound) and secondary gypsum (CaSO 4 .2H 2 O, soft non-binder compound) [30][31][32].…”
Section: Chemical Attacksmentioning
confidence: 99%